Rats: gnawing through the barriers to understanding genetic susceptibility and breast cancer - Blackburn, Anneke C (BioMed Central, 2011)
Advances in genotyping technology have provided us with a large number of genetic loci associated with cancer susceptibility; however, our ability to understand the functional effects of the genetic variants of these loci remains limited. In the previous issue, Smits and colleagues demonstrate the use of congenic rat strains to discover that the Mcs5a breast cancer susceptibility locus is most likely acting through the immune system, via novel transcriptional regulatory mechanisms. This challenges our conventional thinking of cancer susceptibility and gene regulation pathways, and illustrates the potential for rodent models to help us functionally characterize polymorphisms of cancer-associated loci.